(untitled) (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2025)
this article explains that in order to achieve professional success in the STEM field, it is necessary to combine knowledge and skills in STEM with creativity. To meet this need, art is integrated into STEM education, thus forming an educational direction known as STEAM